Upregulation of TREM2 expression in M2 macrophages promotes Brucella abortus chronic infection - Wang, Jingyu; Yan, Zhirong; Zhang, Weiyu; Liu, Xiaofeng; Wang, Jun; Peng, Qisheng (Frontiers in Immunology, 2024)
Brucella abortus (B.abortus) is a zoonotic bacterial pathogen that establishes chronic infections in its host. Eradication of brucellosis with antibiotic therapy is often incomplete or slow. In the mouse model, predominance of the alternatively activated macrophages (also known as M2) play an essential role in sustaining chronic infection. The underlying functional mechanism of how M2 sustain chronic infection remains incompletely understood. Here, we show that B. abortus can enter M2 via triggering receptor expressed on myeloid cells 2(TREM2), and promotes upregulation of TREM2 expression of M2 in type IV secretion system (T4SS) dependent manner. Increased TREM2 enhances B. abortus growth within M2 by suppression of intracellular ROS production, prevention of M2 pyroptosis via suppression mitochondria ROS (mROS), and promotion of M2 proliferation via increasingβ-catenin expression. In line with these results, downregulation of TREM2 expression suppresses B. abortus intracellular growth, M2 proliferation, and induces M2 pyroptosis. In our mouse model, upregulation of TREM2 expression sustains accumulation of M2 and B. abortus chronic infection, whereas downregulation of TREM2 expression restricts M2 proliferation and chronic infection. Collectively, our results suggest targeting TREM2may be used as a potential adjunct to antibiotic therapy for the prevention of Brucella chronic infection.